Monetary Policy And Sectoral Value-Added In SAARC Countries: A Panel ARDL Analysis - SHEIKH, MUHAMMAD RAMZAN; BIBI, ASIA; ABBAS, MAZHAR; TARIQ, MUHAMMAD (The journal of contemporary issues in business and government, 2021)
Every country has two main demand management policies: monetary policy and fiscal policy. This study is an attempt to elucidate the relationship between monetary policy and sectoral value-added in SAARC countries over the period 1990-2020 by applying the panel ARDL technique. The findings of the study suggest that monetary policy has a positive bearing on sectoral value-added in SAARC countries. Moreover, the study has suggested that monetary policymakers must devise the policy by focusing on sectoral growth.